Predicting the development of diabetic retinopathy based on identification of rs759853 and rs9640883 in the AKR1B1 gene (Ukrainian Journal of Ophthalmology, 2026)
Background: Currently, up to 50% of the risk for developing diabetic retinopathy (DR) is attributed to genetics. Identification of patients predisposed to develop DR could facilitate the development of individualized approaches to prevention and treatment of the disease. Associations of the AKR1B1 SNPs rs759853 and rs9640883 with DR have been reported previously.Purpose: To predict the development of DR based on identification of these SNPs in the AKR1B1 gene.Materials and Methods: Four hundred and nine patients were involved in the study. Group 1 comprised 281 patients without DR, and Group 2 comprised 128 patients with DR. TaqMan Mutation Detection Assays (Thermo Fisher Scientific) were used to analyze polymorphic DNA loci in a Real-Time PCR System (7500 system; Applied Biosystems, Foster City, CA). A multiple logistic regression model was built and analyzed to analyze the relationship of the genotype with the risk for developing DT. Statistical analysis was performed using Statistica 10 (StatSoft, Inc., USA) and SPSS Statistics 22 (IBM Corp., USA).Results: A multiple regression model for predicting the development of DR demonstrated sufficient reliability of the effect of independent variables on the estimated index: -2 ? log(likelihood) = 354.467 (?2=42.877; p
Keywords: diabetic retinopathy; AKR1B1; rs759853; rs9640883; prognostic regression models